Quality assessment for stereoscopic images with JPEG compression errors - Voo, Kenny H B; Bong, David B L (Institute of Electrical and Electronics Engineers Inc, 2015)
In this paper a new quality assessment method for stereoscopic image with compression distortion is proposed. This method is designed based on hybrid of 2D image quality metrics and stereoscopic depth map information. The proposed metric is tested on LIVE 3D image database with JPEG and JPEG2000 (JP2K) errors. As a result, this metric has shown an improved performance in assessing perceived quality for stereoscopic images